Analisis Kadar Kafein, Abu, Air dan Sari Kopi Pada Sampel Kopi Bubuk Komersil - M. Bintang Anugrah; Jhonatan Johan Parulian; Delviani Delviani; Nelson Nelson; Rahmi Rahmi (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2022)
Caffeine is a secondary metabolite compound derived from the alkaloid group with its characteristic bitter taste. This study aims to analyze the water content, ash content, coffee extract and caffeine test using the High-Performance Liquid Chromatography (HPLC) method on ground coffee with six different types of ground coffee. The method used for ground coffee analysis refers to SNI 01-3542-2004. In the caffeine content test, the method used refers to SNI 2983:2014 concerning instant coffee. Caffeine was extracted from the sample with water at 90ºC in the presence of magnesium oxide after filtering, the caffeine content in the extract was determined using the HPLC method on the RP-18 column using isoratic elution with UV light detection at a wavelength of 272 nm. Caffeine levels in ground coffee are 1.71%, 2.43%, 0.23%, 2.10%, 2.58% and 6.02%. The maximum amount of caffeine content that is allowed for public consumption per day based on SNI is 0.9-2%.